Observing justice at Guantánamo Bay: human rights NGOs and trial monitoring at the US military commissions - Lohne, Kjersti (Human rights review, 2021)
The article critically considers the role of NGOs at the US naval base in Guantánamo Bay, Cuba. On the basis of observation of pre-trial hearings for the case against Khalid Sheik Mohammed et al.—those allegedly responsible for the September 11 attacks—the article analyses NGOs as trial monitors of the US military commissions set up to deal with ‘alien unprivileged enemy belligerents’. In spite of continued efforts by human rights NGOs and incremental improvements in the military commissions’ institutional arrangements and practice, the article shows how NGOs have become so much a part of the everyday operation of justice at ‘Gitmo’ that they legitimate the military commissions’ claim to be delivering fair and transparent justice.